Use of Fermented Azolla in Diet of Tilapia Fry (Oreochromis niloticus) - Hundare, S. K.; Pathan, D. I.; Ranadive, A. B. (International Journal of Bio-resource and Stress Management, 2018)
The present study was undertaken to evaluate the effect of fermented azolla as fish meal substitute in the tilapia fry diet (Oreochromis niloticus) on growth performance, survival and feed utilization. In the experiment, the fry length initially ranging between (2.160±0.090 cm and 2.540±0.060 cm) and weight initially ranging between (0.190±0.010 g and 0.210±0.010 g) were fed on practical basal diet (30% crude protein) in the form of pellet during rearing period of 60 days. The fermented azolla were incorporated in the experimental diet at various levels such as 0% azolla, 10% fermented azolla, 20% fermented azolla and 30% fermented azolla to formulate four different test diets along with control diet. (Basal diet, without incorporation of fermented azolla, was used as control diet). The experimental fishes were fed with the experimental diet at of 7% of the body weight twice a day. Among the experimental treatments, the treatment 20% fermented azolla showed significantly higher growth parameters such as length gain (178.586±11.313%), weight gain (1346.770±70.251%), specific growth rate (4.449±0.083%), average daily growth (2.840±0.057%) and survival (95.556±2.222%). The feed utilization in terms of feed conversion ratio (1.236±0.030%) was significantly lower in 20% fermented azollathan control group, whereas protein efficiency ratio (4.145±0.169) in 20% fermented azolla showed significantly higher than that of other treatments.